Post-harvest losses in rural-urban value chains: Evidence from Ethiopia - Minten, Bart; Tamru, Seneshaw; Reardon, Thomas (Elsevier, 2021)
We study post-harvest losses (PHL) in important and rapidly growing rural–urban value chains in Ethiopia. We analyze self-reported PHL from different value chain agents – farmers, wholesale traders, processors, and retailers – based on unique large-scale data sets for two major commercial commodities, the storable staple teff and the perishable liquid milk. Aggregate PHL over all segments of the value chain (farmer to retailer) in the most prevalent marketing channel for teff and milk amount to between 2.2 and 3.3 percent and 2.1 and 4.3 percent of total produced quantities, respectively. Estimates of PHL from this research are found to be lower than is commonly assumed. We complement these findings with primary data from urban food retailers for more than 4,000 commodities. We find that the emerging modern retail sector in Ethiopia is characterized on average by half the level of PHL than is observed in the traditional retail sector. This is likely due to more stringent quality requirements in procurement systems, to sales of more packaged – and therefore better protected – commodities, and to better refrigeration, storage, and sales facilities. The further expected expansion of modern retail in these settings should therefore likely lead to a lowering of PHL in food value chains, at least at the retail level.